Effectiveness of Mindfulness Intervention to Reduce Burnout in Intensive Care Nurses: A Systematic Review - Sukmayanti, Luh Putu; Nursalam, Nursalam; Makhfudli, Makhfudli (Poltekkes Kemenkes Jakarta III, 2024)
Nurses need proper self-management to deal with emotions caused by burnout. One of the meditations that nurses can do is focus attention or mindfulness. Mindfulness is a form of self-regulation strategy that involves focusing attention, responding to thoughts, sensations, and emotions with an attitude of acceptance, without judgment, and being aware of current situations and events. This study aimed to examine of a mindfulness intervention that can reduce burnout in intensive care nurses. Design study a systematic review, the sample used was intensive care nurses, variables are mindfulness intervention and burnout. Mindfulness-based interventions (yoga or meditation, music therapy, cognitive relaxation, breathing relaxation, stress management). Were searched using four databases published through February 2024. A total of 15 RCT and Quasi-Experimental were included in the final analysis. Mindfulness-based interventions (yoga or meditation, music therapy, cognitive relaxation, breathing relaxation, stress management). Effective mindfulness programs are generally carried out for 12-8 weeks with weekly meetings for 2 hours and intensive training between meetings. Overall, the modalities appeared to alleviate and reduce burnout (p<0,001). Mindfulness-based interventions appear to alleviate can reduce burnout in intensive care nurses. Future studies look at mindfulness-based interventions among nurses using more rigorous approaches and larger samples.